2012
DOI: 10.1002/0471140864.ps2122s70
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Fingerprinting of Complex Biological Samples Using Combinatorial Libraries of Fluorogenic Probes

Abstract: Proteases have garnered interest as candidate biomarkers and therapeutic targets for many human diseases. A key challenge is the identification and characterization of disease-relevant proteases in the complex milieu of biological fluids such as serum, plasma and bronchoalveolar lavage, in which a multitude of hydrolases act in concert. We have successfully utilized a concise combinatorial library of internally quenched fluorogenic peptide probes (IQFPs) to map the global proteolytic substrate specificities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…Several caveats should be noted when interpreting our data based on the library characteristics and are discussed in our previous publications . While the results presented here are observed from a single donor, the results match the previous observations .…”
Section: Resultssupporting
confidence: 80%
“…Several caveats should be noted when interpreting our data based on the library characteristics and are discussed in our previous publications . While the results presented here are observed from a single donor, the results match the previous observations .…”
Section: Resultssupporting
confidence: 80%
“…Protease assays were performed with the specified substrates as previously described (Jambunathan et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…We profiled the plasma proteolytic activity under classical serine protease conditions for two important reasons: first, serine proteases are the most abundant class of proteases in plasma, and second, evidence points to serine class protease involvement in FSGS [Carraro et al., ]. Moreover, our preliminary optimization of buffer space using nonspecific probes indicated that maximal proteolytic activity for plasma was observed under serine protease buffer conditions [Jambunathan et al., ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, each well of the library contains an equimolar mixture of up to eight individual IQFPs. A more detailed description of this library is provided elsewhere [Watson et al, 2011, Jambunathan et al, 2012a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation